Current Conservative Treatment and Management Strategies of Skeletal Muscle Injuries - Hotfiel, Thilo; Carl, H-D.; Swoboda, Bernd; Heinrich, Marc Christopher; Heiß, Rafael; Grim, C.; Engelhardt, M. (Zeitschrift für Orthopädie und Unfallchirurgie, 2016)
Muscle injuries frequently occur during sport and are one of the commonest injuries. The diagnosis and treatment of muscle injuries impose high demands on medical treatment, in order to ensure successful regeneration and a rapid return to sport. Most of the injuries can be treated conservatively, as skeletal muscles have a high endogenous capacity for repair and regeneration. Conservative treatment includes initial on-field therapy. This is known as the "RICE" principle and is common and recommended for initial treatment for most sports injuries. The primary therapy target is to reduce pain, swelling and bleeding and thus to limit the initial inflammatory process and prevent further damage. During the first days after injury, brief immobilization helps to reduce the re-injury rate and accelerates the formation of granulation tissue. There are many possible additional treatments, including intramuscular injections, manipulation of the sacroiliac joint or rehabilitation programs, including stretching and strengthening. If the acute treatment phase is complete after 3 to 5 days, more active treatment, including trunk stabilisation, stretching and strengthening, can be started gradually. Despite their high prevalence, there have only been a few studies on the treatment and management of these injuries. The aim of this manuscript is to review the literature on the classification, pathobiology and treatment strategies for muscle injuries.
EVALuna2:10907